Ethnic disproportionality in the identification of high incidence Special Educational Needs: a national longitudinal study ages 5-11 - Strand, S; Lindorff, A (SAGE Publications, 2021)
We used pupil level data from the National Pupil Database in England to conduct a longitudinal analysis of the identification of Moderate Learning Difficulties (MLD) and Social, Emotional and Mental Health (SEMH) difficulties among 550,000 pupils from ages 5-11 years. Survival analysis was used to determine the Hazard Ratios (HRs) for time to first identification, controlling for prior attainment and social-emotional development at age 5 as well as socio-economic variables. For MLD, the over-representation of Black Caribbean and Pakistani pupils compared to White British pupils was eliminated following age 5 controls, and the predominant picture was of ethnic minority under-representation. For SEMH, Black Caribbean and Mixed White and Black Caribbean (MWBC) pupils continued to be over-represented even after age 5 controls (HR=1.36 and 1.44 respectively), although this was not true for the larger group of Black African pupils who were under-represented in the adjusted analyses (HR=0.62), as were most other ethnic minority groups. The results indicate most ethnic minority groups are under-represented for SEN after adjusting for pupil characteristics on-entry to school, though this varies by ethnic group and type of need.